2003
DOI: 10.1053/jhep.2003.50416
|View full text |Cite
|
Sign up to set email alerts
|

Inhibition of HBV replication by siRNA in a stable HBV-producing cell line

Abstract: Potent inhibition of endogenous gene expression by RNA interference has been achieved by using sequence-specific posttranscriptional gene silencing through the action of small interfering RNA molecules (siRNA). In these reports, the natural function of genes could be deduced through the ensuing loss of function. Based on the extraordinary effectiveness in silencing endogenous genes, we wondered whether siRNA could be applied against viral replication in a hepatitis B virus (HBV) model using HBV-specific siRNA.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

1
13
0

Year Published

2004
2004
2021
2021

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 71 publications
(14 citation statements)
references
References 39 publications
1
13
0
Order By: Relevance
“…R ibonucleic acid interference is a naturally occurring mechanism for silencing homologous genes. 1,2 Synthetic and plasmid-based siRNA expression systems are both effective at suppressing HBV infection, in vitro and in vivo, [3][4][5][6][7][8][9] providing the basis for a new therapeutic strategy against HBV. However, the absence of a suitable delivery system presents a major obstacle against their clinical use.…”
mentioning
confidence: 99%
“…R ibonucleic acid interference is a naturally occurring mechanism for silencing homologous genes. 1,2 Synthetic and plasmid-based siRNA expression systems are both effective at suppressing HBV infection, in vitro and in vivo, [3][4][5][6][7][8][9] providing the basis for a new therapeutic strategy against HBV. However, the absence of a suitable delivery system presents a major obstacle against their clinical use.…”
mentioning
confidence: 99%
“…Several therapeutic strategies against HBV, such as interferon-α (3), nucleotide analogues (19-21), antisense DNA (22), ribozyme (23) and RNA interference (24,25), have been reported in clinical or laboratory investigations. However, to date no ideal treatment for HBV eradication has been reported.…”
Section: Discussionmentioning
confidence: 99%
“…Several groups have reported using siRNAs to inhibit HBV replication in cell cultures and animal models [12][13][14][15][16][17][18][19] . Although all of these reports showed that HBV replication was inhibited to various degrees by siRNAs, several factors must be taken into account before siRNAs are used to treat HBV infection.…”
Section: Discussionmentioning
confidence: 99%
“…The physiological functions of RNAi are not very clear as yet, but it has been used successively as a potent method of gene knockdown in study of gene function and in experimental treatment of some diseases [4][5][6][7][8][9][10][11][12][13][14][15][16][17][18][19] . In mammalian cells, double-stranded RNAs inducing RNAi must be short in length (<30 bp) so that they would not activate nonspecific interferon reactions.…”
Section: Introductionmentioning
confidence: 99%